Analisis Kesalahan Penulisan Pada Berita Online CNBC Indonesia Untuk Mengurangi Ambiguitas Pemahaman Pembaca (International Forum of Researchers and Lecturers, 2023)
The use of standard language is used in writing news. This research aims to identify and analyze writing errors made by journalists in writing news on internet media, especially on CNBC Indonesia. The research method used is descriptive qualitative, focusing on Indonesian writing errors from the aspects of spelling and diction. The research results show that there are several errors that often occur in news writing on CNBC Indonesia, such as inappropriate use of punctuation, letter writing errors, and word writing errors. These errors can confuse readers and create ambiguity in understanding. Recommendations that can be given are to increase accuracy in the use of punctuation marks, letters and words. Journalists need to pay attention to correct writing rules and double-check before publishing news. Apart from that, the editorial team also needs to provide training and guidance to journalists to improve the quality of news writing. It is hoped that the results of this research can contribute to improving the quality of CNBC Indonesia's online news writing and reducing ambiguity in reader understanding. This is important to maintain media professionalism and provide clear and accurate information to readers. In this way, it is hoped that CNBC Indonesia's online news can become a reliable source of information that is easy for readers to understand.